Scenario-based interviews : developing studies of policy and practice - Beighton, Christian, 1970- (SAGE research methods cases, 2021)
This case discusses how scenario-based interviews can be used to develop research into policy and practice. Based on data collected from U.K. further education management settings, it shows how and why scenario-based interviews were used. It also explains how the data collected were then used to illustrate and analyze the implementation of a controversial policy in these settings. After a brief overview of the project, its rationale, and its context, I discuss the research design, explaining how and why a scenario-based approach to data collection was chosen. The practicalities of doing the research in this way is then discussed, along with the various difficulties encountered during the project and the practical lessons learned therein. These include the need to respect professional ethics, the question of working with potentially sensitive data, and presenting and analyzing extremely diverse findings in ways that matched the spirit of a scenario-based approach. My conclusion highlights two significant advantages of scenario-based interviews in this kind of setting. The first advantage is that the approach facilitates the collation of comparable data in a meaningful way in a single study. The second advantage is that the approach responds to the kind of working practices and experiences, often based in professional problem-solving, that the interviewees themselves commonly used. This, I suggest, increases the level of trust and the quality of data as the interviewees see that the interviewer understand their environment and its complexity. These findings are therefore applicable to a wide range of other education settings.